Think simple : how smart leaders defeat complexity - Segall, Ken (Portfolio / Penguin, 2016)
"Simplicity is arguably the most potent weapon in business--attracting customers, motivating employees, helping outthink competitors, and creating new efficiencies. Yet rarely is it as simple as it looks"-- Provided by publisher